HASIL ANALISIS STATISTIK, DIFERENSIAL, DAN KUALITAS CITRA TERHADAP KOMPOSISI LOGISTIC CIRCLE MAP - Makmun Makmun (Asosiasi Dosen Muda Indonesia, 2023)
The problem of data security is still a matter of concern in the digital era like today. An effective security method is needed and it is difficult to break into. Encryption is an effective method of ensuring data security. The encryption algorithm is built using a chaotic cipher base so that performance in securing data and information increases. The new chaotic composition resulting from two chaotic maps will have better randomness. Logistic Map and Circle Map were chosen because they have good randomness. The new chaotic composition is called the Logistic Circle Map (LC Map). By bifurcation diagram test, Lyapunov Exponent, and NIST random test, the best density occurs at X_0=0.9 , K = 1000, r = 3.7 and Ω = 0.4. The new chaotic composition parameters have passed all 16 NIST (National Institute of Standards and Technology) tests. There are four parameters used in this study in order to obtain a sufficiently high key space, namely 1.296 ×〖 10〗^84 combinations and having a high level of lock sensitivity of 10−17. The image encryption algorithm of the LC Map function has high resistance against various attacks. This can be proven by carrying out key space tests, sensitivity tests for key spaces, histogram tests, entropy, correlation coefficients, and differential tests using the UACI NPCR. The test results on digital image decryption using the Mean Square Error (MSE) show a result of 0 and the Peak Signal to Noise Ratio (PSNR) shows a result of ∞. That is, the encrypted image is similar to the original image.